2011
DOI: 10.1521/soco.2011.29.3.288
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Rationalization: Increased Support for Large-Scale and Small-Scale Social Systems Following System Threat

Abstract: System justifi cation theory suggests that individuals defend and rationalize aspects of prevailing social systems, especially in response to system threat.In two experiments we extend this framework by demonstrating that people rationalize small-scale social systems (e.g., local popularity hierarchies and the nuclear family) as well as large-scale social systems (e.g., American society). Furthermore, we fi nd that system threat leads people to bolster not only the legitimacy of the social system that is direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…We used a French translated version from Wakslak et al (2011) adaptation of Kay and Jost's (2003) scale for a high school population. We added a ninth item to tap the meritocracy dimension of the scale (see below).…”
Section: Methodsmentioning
confidence: 99%
“…We used a French translated version from Wakslak et al (2011) adaptation of Kay and Jost's (2003) scale for a high school population. We added a ninth item to tap the meritocracy dimension of the scale (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Wakslak et al (2011) have argued that once a system justification motive has been activated via system threat, individuals may aim to justify the system at different levels, from microscale systems such as families and friendship cliques to larger-scale systems such as national economies. Their results suggest that individuals may defend multiple social systems even when only one system has been threatened, an effect they call spreading rationalization.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that this reference to the motive to see parts of the status quo as ''natural'' goes back to the original Jost and Banaji (1994) work, as well as having resonances in recent views about injunctification, the idea that ''people may be motivated to view the status quo, even if unfair, as the most desirable state of affairs'' (Kay et al, 2009, p. 421). Additionally, Wakslak, Jost and Bauer (2011) found that critiques of one part of the social system caused people to bolster other parts of the social system. In reference to that study, Jost et al (2015) suggest that ''a threat to the legitimacy or stability of one aspect of the social system stimulates defensive responding on behalf of other parts of the system'' (p. 330).…”
Section: Discussionmentioning
confidence: 99%